Studi Analisa Tentang Rapture Sebagai Pembuktian Kebenaran Doktrin Pre-Tribulasi - Febrianto, Carles (JURNAL ILUMINASI, 2024)
Research on the rapture or what is often referred to as the rapture of the church in the pre-tribulation period aims to find the right answer based on Bible truth so that God's people do not experience confusion in believing a new teaching that appears. the difference in perception in interpreting the biblical text in the world of theology causes the interpretation of the truth of the teaching of the rapture of the church that occurred in the pre-tribulation period to be blurred. The church today is being faced with various eschatological teaching concepts, especially the rapture of the church, which demands a definite proof of a truth. Therefore, the research is intended to prove and provide an argument for the truth of the pre-tribulation teaching worthy of belief among believers. as for this study using a qualitative method, namely digging the texts in the Bible inductively to prove the truth of pre-tribulation. the results of this study found that the teaching of the rapture that occurred in the pre-tribulation period is a true teaching and is based on the Bible.